2018
DOI: 10.4314/bajopas.v10i1.63s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of level of toxic heavy metal (PB) in local and foreign brands of lipsticks in FCT, Abuja, Nigeria

Abstract: This study determined toxic heavy metal concentration in Local andand 70% of the samples were not safe for the average users. While the ingested daily intake in the Local and the Foreign samples indicated 50% and 90% of the samples were also not safe for high users as compared to WHO limit (20 µg/g) for Lead specified in cosmetic. Thus, continuous usage of these lipsticks can increase rate of exposure of the body system to Lead related disease conditions such as cancer which is known to be detrimental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Comparison according to FDA According to the results reported by the Food and Drug Administration (FDA) on the Pb content in lipsticks in 2011, the limit value for Pb as a color additive in cosmetics is 20 μg/g (6,29). It was found that only 33% of all brands and colors of lipsticks had Pb content less than the FDA limit that was related to French brand.…”
Section: Effect Of Colormentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison according to FDA According to the results reported by the Food and Drug Administration (FDA) on the Pb content in lipsticks in 2011, the limit value for Pb as a color additive in cosmetics is 20 μg/g (6,29). It was found that only 33% of all brands and colors of lipsticks had Pb content less than the FDA limit that was related to French brand.…”
Section: Effect Of Colormentioning
confidence: 99%
“…Recently, the occurrence of heavy metals pollution in cosmetics has attracted worldwide attention. Lead (Pb) and cadmium (Cd) are two potentially harmful heavy metals that cause considerable concerns (5,6). Pb contamination in cosmetics can originate from Pb solder, lead-based dyes in production material or from contaminated dust.…”
Section: Introductionmentioning
confidence: 99%